Effect of Paracetamol (Acetaminophen) on Body Temperature in Acute Ischemic Stroke: A Double-Blind, Randomized Phase II Clinical Trial - Dippel, D. W.J.; van Breda, E. J.; van Gemert, H. M.A.; van der Worp, H. B.; Meijer, R. J.; Kappelle, L. J.; Koudstaal, P. J. (Stroke, 2001)
Background and Purpose —Body temperature is a strong predictor of outcome in acute stroke. However, it is unknown whether antipyretic treatment leads to early and clinically worthwhile reduction of body temperature in patients with acute stroke, especially when they have no fever. The main purpose of this trial was to study whether early treatment of acute ischemic stroke patients with acetaminophen (paracetamol) reduces body temperature. Methods —Seventy-five patients with acute ischemic stroke confined to the anterior circulation were randomized to treatment with either 500 mg (low dose) or 1000 mg (high dose) acetaminophen or with placebo, administered as suppositories 6 times daily during 5 days. Body temperatures were measured with a rectal electronic thermometer at the start of treatment and after 24 hours and with an infrared tympanic thermometer at 2-hour intervals during the first 24 hours and at 6-hour intervals thereafter. The primary outcome measure was rectal temperature at 24 hours after the start of treatment. Results —Treatment with high-dose acetaminophen resulted in 0.4°C lower body temperatures than placebo treatment at 24 hours (95% CI 0.1°C to 0.7°C). The mean reduction from baseline temperature with high-dose acetaminophen was 0.3°C (95% CI 0°C to 0.6°C) higher than that in placebo-treated patients. Treatment with low-dose acetaminophen did not result in lower body temperatures. After 5 days of treatment, no differences in temperature were found between the placebo and the high- or low-dose acetaminophen groups. Conclusions —Treatment with a daily dose of 6000 mg acetaminophen may result in a small, but potentially beneficial, decrease in body temperature shortly after ischemic stroke, even in normothermic and subfebrile patients. Further studies should determine whether this effect is reproducible and whether early reduction of body temperature leads to improved outcome.